A universal dental adhesive containing copper nanoparticles stabilizes the hybrid layer in eroded dentin after 1 year. (March 2022) - Hanzen, Taíse Alessandra; Gutiérrez, Mario Felipe; de Paris Matos, Thalita; Mara de Paula, Alexandra; Figueredo de Siqueira, Fabiana Suelen; Millán Cardenas, Andrés Felipe; Viteri-Garcia, Andres; Hernandez, Marcela; Loguercio, Alessandro D.; Reis, Alessandra
Abstract: This study evaluated the matrix metalloproteases (MMP) inhibition of the copper nanoparticles (CuNp), and the effects of their addition into a universal adhesive system on antimicrobial activity (AMA), ultimate tensile strength (UTS), water sorption (WS), solubility (SO), as well as the 24h and 1y microtensile bond strength (μTBS), nanoleakage (NL) and in situ degree of conversion (DC), on sound and eroded dentin. Anti-MMP activity was evaluated for MMP-2, -8 and -9. CuNp (0%[control] and 0.1 wt%) were added into Ambar Universal. Antimicrobial activity against S. mutans was tested using agar diffusion. For UTS, specimens were tested after 24h and 28d. WS and SO were evaluated during 56d. After induced erosion, adhesives and composite were applied to flat dentin surfaces, and specimens were sectioned to obtain resin–dentin sticks, which were used for evaluation of μTBS and nanoleakage at the 24h and 1y periods. DC was evaluated at the 24h period in these beam-like specimens. Data were submitted to appropriate statistical analyses (α = 0.05). CuNp demonstrated anti MMP-activity ( p < 0.05) besides providing antimicrobial activity ( p < 0.05), as well as maintained stable μTBS and NL values over 1-year, for both substrates ( p < 0.05). Thus, CuNp may prevent the degradation of the adhesive interface, mainly in eroded dentin. Clinical relevance: Copper-containing universal adhesives could be considered a feasible alternative to improve adhesive properties to sound and eroded dentin after 1-year.